Citizen Research Potential Cognition and Preserving of Historic-Cultural Heritage by Means of History Education - Verbyts’ka, Polina (Pedagogical Discourse, 2013)
The article deals with the topical problem of bringing up in youth value attitude to historical and cultural heritage. Monuments of history and culture of a community are unique evidence of the past, an important source of historical experience containing versatile information about the society’s development in the past and present. At the same time historical and cultural monuments as achievements of mankind contribute to young personality’s formation, his/her spiritual development, formation of constant feeling of belonging to local community. In the process of perception and formation of value attitude of an individual to preserving historical and cultural heritage young people learn to make independent decisions, make well-considered choice and forecast the society’s development in the future.